IL-18 Blockage Reduces Neuroinflammation and Promotes Functional Recovery in a Mouse Model of Spinal Cord Injury - Easmin Begum; Md Rashel Mahmod; Md Mahbobur Rahman; Fumiko Fukuma; Takeshi Urano; Yuki Fujita (Biomolecules)
The prognosis of spinal cord injury (SCI) is closely linked to secondary injury processes, predominantly driven by neuroinflammation. Interleukin-18 (IL-18) plays a pivotal role in this inflammatory response. In previous work, we developed an anti-IL-18 antibody capable of neutralizing the active form of IL-18. This study evaluated the functional effects of this antibody in a mouse model of SCI. IL-18 expression was significantly upregulated in the spinal cord following injury. In a mouse model of SCI (C57BL/6J strain), mice were administered 150 μg of the anti-IL-18 antibody intraperitoneally. IL-18 inhibition via antibody treatment facilitated motor functional recovery post-injury. This intervention reduced neuronal death, reactive gliosis, microglia/macrophage activation, and neutrophil infiltration. Additionally, IL-18 inhibition lowered the expression of pro-inflammatory factors, such as IL-1β and the M1 microglia/macrophage marker Ccl17, while enhancing the expression of the M2 microglia/macrophage marker Arginase 1. Collectively, our findings demonstrate that IL-18 inhibition promotes motor recovery and facilitates the polarization of M1 microglia/macrophages to the M2 phenotype, thereby fostering a neuroprotective immune microenvironment in mice with SCI.